2016
DOI: 10.1017/s0305000916000477
|View full text |Cite
|
Sign up to set email alerts
|

Morphological awareness as a function of semantics, phonology, and orthography and as a predictor of reading comprehension in Chinese

Abstract: This study investigates the contributions of semantic, phonological, and orthographic factors to morphological awareness of 413 Chinese-speaking students in Grades 2, 4, and 6, and its relationship with reading comprehension. Participants were orally presented with pairs of bimorphemic compounds and asked to judge whether the first morphemes of the words shared a meaning. Morpheme identity (same or different), whole-word semantic relatedness (high or low), orthography (same or different), and phonology (same o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 41 publications
6
35
1
1
Order By: Relevance
“…In addition, the study also found that vocabulary knowledge was a significant predictor of the development of compounding awareness in Chinese from Grades 3 to 4. This result is consistent with previous findings that vocabulary knowledge contributed to the development of compounding awareness (Cheng et al, 2015; Kuo & Anderson, 2006; Li, Dronjic et al, 2017; McBride‐Chang et al, 2008). As mentioned, with the accumulation of vocabulary, children have access to a greater number of opportunities to develop a deeper understanding of critical morphemes and extract the structure of words, and thus promote the development of compounding awareness (Kuo & Anderson, 2006).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the study also found that vocabulary knowledge was a significant predictor of the development of compounding awareness in Chinese from Grades 3 to 4. This result is consistent with previous findings that vocabulary knowledge contributed to the development of compounding awareness (Cheng et al, 2015; Kuo & Anderson, 2006; Li, Dronjic et al, 2017; McBride‐Chang et al, 2008). As mentioned, with the accumulation of vocabulary, children have access to a greater number of opportunities to develop a deeper understanding of critical morphemes and extract the structure of words, and thus promote the development of compounding awareness (Kuo & Anderson, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…As one code‐related skill, Chinese compounding awareness – ‘the understanding of how morphemes can be combined sensibly in the Chinese language’ (Liu & McBride‐Chang, 2010, p. 63) – may be a significant contributor to vocabulary acquisition. Specifically, compounding awareness might help children to speculate about the meaning of morphologically complex words mediated through the smaller parts children are already familiar with, which is the case in both alphabetic languages (e.g., Carlisle & Fleming, 2003) and Chinese (e.g., Chen, Hao, Geva, Zhu, & Shu, 2009; Li, Dronjic et al, 2017; McBride‐Chang et al, 2008).…”
Section: Highlightsmentioning
confidence: 99%
“…Morphological awareness has been shown to be a unique contribution to reading comprehension across languages beyond substantive controls (e.g., Saiegh-Haddad and Geva, 2008; Deacon et al, 2014; Ruan et al, 2018). Morphological awareness plays an important role in reading development in Chinese (Shu et al, 2006; Liu and McBride-Chang, 2010; Cheng et al, 2017) and it involves the integration of semantic, phonological, and syntactic information (Hanley, 2005; Li et al, 2017). Extensive research has shown that morphological awareness is a stronger correlate of reading comprehension than phonological awareness in Chinese, due to the morphosyllabic nature of Chinese (see a meta-analysis, in Ruan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More than 75% of Mandarin Chinese words are compounds, composed of two or more morphemes or characters (Kuo and Anderson, 2006), and very few inflectional and derivational words exist in Chinese. In addition, Mandarin Chinese has been evolving in the direction of making its syllables ever shorter and structurally simpler, which results in a vast number of homophones (e.g., /xi1/ “west” and /xi1/ “brook”) and homonyms (/hua1/ “flower”, “spend”) among words (Shu and Anderson, 1997; Li et al, 2017). Research shows that about 70%, or approximately 1,300 Mandarin syllables represent more than one morpheme, and on average one syllable corresponds to five morphemes or characters (Tang, 1995; Shu and Anderson, 1997; Duanmu, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, os estudos têm demonstrado que: a consciência morfológica contribui de forma única para o desempenho em compreensão; pode estar alterada em grupos de disléxicos ou de pessoas com problemas de aprendizagem; e o uso de programas de treinamento pode proporcionar resultados melhores em compreensão leitora (p. ex., Diamanti et al, 2017;Law, Wouters, & Ghesquière, 2015;Li, Dronjic et al, 2017;Lyster, Lervåg, & Hulme, 2016;Manolitsis, Grigorakis, & Georgiou, 2017;Tighe & Schatschneider, 2016b). Corroborando esses achados, uma meta análise recente (Tighe & Schatschneider, 2016a) Tendo em vista a importância da consciência morfológica para os processos de alfabetização e desempenho em leitura e escrita (Mota, 2009), assim como da importância da avaliação de diferentes habilidades metalinguísticas para se investigar possíveis dificuldades em habilidades de ordem superior (como a compreensão da leitura) e traçar planos diagnósticos e interventivos (Spinillo, Cloze e em tarefas de consciência morfológica, investigando os efeitos da idade e do ciclo escolar nesses construtos; (2) investigar a correlação entre estas habilidades e o poder preditivo da consciência morfológica no desempenho em compreensão leitora.…”
Section: Introductionunclassified